Capability of the SMHI‐RCA4 RCM driven by the ERA‐Interim reanalysis to simulate heat waves in Argentina. (12th July 2017) - Collazo, Soledad; Lhotka, Ondřej; Rusticucci, Matilde; Kyselý, Jan
ABSTRACT: The aim of the work was to evaluate the capability of the SMHI‐RCA4 regional climate model (RCM) driven by the ERA‐Interim reanalysis to simulate heat waves in Argentina. Firstly, we evaluated simulations of summer daily maximum temperature (Tmax) against observed data from nine stations. The model showed a warm Tmax bias at six locations and the smallest and/or negative biases were located over regions with complex topography. Heat waves were defined based on exceedances of the daily 90th percentile of Tmax at individual stations. The model overestimated the intensity, duration, and number of heat waves at all locations, but more intense heat waves were underestimated. In particular, we analysed the extreme heat wave that occurred in November 1985 in northeastern Argentina and found out that a possible reason for its underestimation was an inaccurate simulation of the sea level pressure gradient in the region. The weaker pressure gradient in the model caused a reduction of the warm northerly advection. Finally, we studied how the parameters of heat waves varied among different phases of El Niño‐Southern Oscillation (ENSO) for observed and modelled data. At five stations, the strongest heat waves occurred during La Niña years and were probably associated with the decrease in precipitation. Abstract : Heat waves are associated with significant societal and economic impacts. It is important to assess capability of models to represent heat waves due to their aforementioned impacts. The simulation of heat waves in the SMHI‐RCA4 RCM exhibited substantial deficiencies over Argentina despite being driven by the ERA‐Interim reanalysis. The SMHI‐RCA4 RCM overestimated the intensity, duration, and number of heat waves at all locations, but more intense heat waves were underestimated.